1984
DOI: 10.1111/j.1399-6576.1984.tb02140.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Activity in Patients Undergoing Upper Abdominal Surgery: Relationship to the Endocrine Stress Response

Abstract: Natural killer (NK) cell activity and the endocrine response during and after parietal cell vagotomy were studied in two groups of patients receiving either epidural analgesia extending from S5 to Th4 + general anaesthesia (Group I), or general anaesthesia (Group II). NK cell activity of unseparated mononuclear cells in peripheral blood was measured against K-562 target cells in a 51Cr-release assay. NK cell activity increased in the same way in both groups in relation to premedication, anaesthesia and surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
2
7

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 26 publications
4
25
2
7
Order By: Relevance
“…Analysis of the data revealed that NK cytotoxic activity in dogs was significantly lower 24 hr after anesthesia. These findings agree with the results of a human study [14]. However, in that report [14], surgical procedures had been performed in addition to the anesthesia.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Analysis of the data revealed that NK cytotoxic activity in dogs was significantly lower 24 hr after anesthesia. These findings agree with the results of a human study [14]. However, in that report [14], surgical procedures had been performed in addition to the anesthesia.…”
Section: Discussionsupporting
confidence: 81%
“…These findings agree with the results of a human study [14]. However, in that report [14], surgical procedures had been performed in addition to the anesthesia. As our finding is based on the use of anesthesia without surgery, the combination of anesthesia and operation Samples were obtained before anesthesia (baseline) and 24, 120 and 192 hr after the anesthesia, and anesthesia then was induced with propofol and maintained with isoflurane for 3 hr; blood samples were obtained from the control dogs at the same time points as for the anesthetized dogs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…T helper cells are a subset of T lymphocytes pivotal in augmenting both cell-mediated [3] and humoral immunity [4]. Major surgery causes changes in the immune response which are related to the extent of surgical trauma [5] and the neuroendocrine stress response [6]. In this study we compared the effects of propofol infusion anaesthesia and combined isoflurane anaesthesia on the immune response to abdominal hysterectomy.…”
mentioning
confidence: 99%
“…A greater number of chemical-specific antibodies has been noted after exposure to building materials in remodeling (21). Suppression of mitogenesis (22) and natural killer cell (NK) function (23) has been described following anesthesia induced by petrochemical agents. Reduced NK function in multiple chemical sensitivity (MCS) patients also has been reported by Heuser (24).…”
Section: Introductionmentioning
confidence: 99%